A Study on the Security of Wireless Networks: Efficient Clustering Algorithms for Wireless Sensor Networks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A wireless sensor network is a self-sufficient system of sensor nodes. It has a Base Station and sensor nodes. Sensor nodes collect information from their environment and send it to the Base Station. Heterogeneous sensor network contains high energy sensor nodes just as low energy nodes. A single-tier network can cause the gateway to overload with the increase in sensors density. Such overload may cause latency in correspondence and inadequate following of events. What's more, the single-tier architecture isn't scalable for a larger set of sensors covering a wider area of interest because the sensors are regularly not capable of long stretch correspondence. Hierarchical clustering is especially useful for applications that require adaptability to hundreds or thousands of nodes. Versatility in this context implies the need for load adjusting and eﬃcient resource use.All nodes in a network can be organized in hierarchical structures called clusters. Each cluster comprises of a cluster head and several member nodes. The member nodes collect information and send it to their cluster heads. The cluster head aggregates and transmits the information to the Base Station. The energy utilization of cluster heads is higher than that for member nodes. Clustering calculations are required which can efficiently utilize the energy of nodes so life of network can be increased. Here we are proposing Fluffy Rationale based clustering for homogenous sensor networks.